Influence of manganese on the microstructure and mechanical properties of oxide-dispersion-strengthened steels. (15th November 2019) - Ashong, Andrews Nsiah; Na, Min Young; Kim, Hyoung Chan; Noh, Sang Hoon; Park, Taesung; Chang, Hye Jung; Kim, Jeoung Han
Abstract: A novel high-Mn oxide-dispersion-strengthened (ODS) steel, with high cryogenic temperature impact energy, was developed. The effect of Mn content on the microstructure and mechanical properties of ODS steels were examined. The addition of 25 wt.% Mn to ODS steel resulted in transformation from a full ferrite phase to austenite and εhcp -martensite phases. ODS steel without added Mn contained a high number density of fine Y-Ti-O oxide particles. In contrast, ODS steel with 25 wt.% Mn contained TiMn2 O4 and relatively coarser Y2 Ti2 O7 oxide particles with lower number densities. The TiMn2 O4 particles showed a crystallographic orientational relationship with the matrix phase. In addition, a high density of deformation twins were formed in tensile-deformed ODS steel with 25 wt.% Mn, but were absent in tensile-deformed ODS steel without added Mn. The ODS steel containing 25 wt.% Mn exhibited higher room-temperature tensile ductility and higher Charpy impact energy at cryogenic temperature without Mn due to the existence of deformation twins, austenite phase, and εhcp -martensite phase in the former. Graphical abstract: Unlabelled Image Highlights: Agglomerates of TiMn2 O4 and Y2 Ti2 O7 nano-particles were seen in Mn-added oxide-dispersion-strengthened steel. TiMn2 O4 nano-particle had a coherent interface with the austenite matrix. High density of deformation twins occurred in tensile deformed Mn-added ODS steel, but were absent in ODS steel without Mn. Mn-added ODS steel exhibited larger room temperature ductility and higher Charpy impact toughness at cryogenic temperature.